Comparison of conventional preparation with modified access preparation on fracture resistance of primary molars - A finite element analysis - Harshini Nivetha Easwaran; Kavitha Swaminathan; Selvakumar Haridoss; M.S. Muthu; Priya Jayakumar (Elsevier, 2023)
Objective: To investigate the influence of Conventional Straight (CS) line and Modified Straight (MS) line access preparations with various restorative materials on the fracture resistance of primary molars using Finite Element Analysis (FEA). Methodology: Three FEA models for each of the primary molars were divided into Group I- Intact tooth model; Group II- Model with CS outline and Group III- Model with MS outline. Based on the restorative material used, Group II and III were further subdivided into subgroup 1- GIC restoration, subgroup 2 - composite resin with GIC base and subgroup 3- Stainless Steel Crown (SSC). Each model was subjected to 5 different force loads directed at the occlusal surface. Maximal von Mises (VM) stresses calculated from stress distribution patterns. Result: The maximum displacement, in all the models of primary molars were seen in GIC restored models in molars with both CS and MS access whereas the minimal displacement was seen in the SSC restored molars of MS group. Conclusion: In primary maxillary second molar and mandibular first and second molar with intact marginal ridges, the fracture resistance of tooth with MS outline restored with GIC base followed by Composite resin was comparable with the tooth restored with SSC and CS outline. Clinical outcome: Based on the results of this FEA analysis, composite restorations with MS outline would be appropriate for endodontically treated primary molars that have intact margins.